Mixed-signal embedded systems design a hands-on guide to the Cypress PSoC - Currie, Edward H. (Springer, 2021)
This textbook introduces readers to mixed-signal, embedded design and provides, in one place, much of the basic information to engage in serious mixed-signal design using Cypress' PSoC. Designing with PSoC technology can be a challenging undertaking, especially for the novice. This book brings together a wealth of information gathered from a large number of sources and combines it with the fundamentals of mixed-signal, embedded design, making the PSoC learning curve ascent much less difficult. The book covers, sensors, digital logic, analog components, PSoC peripherals and building blocks in considerable detail, and each chapter includes illustrative examples, exercises, and an extensive bibliography. Provides a hands-on guide to designing mixed-signal embedded systems with Cypress PSoC; Treats in detail all major PSoC topics and building blocks; Provides insight into the historical development of embedded systems; Uses a sufficient amount of mathematical rigor to serve as a textbook and includes in each chapter illustrative examples, exercises, and an extensive bibliography.